Sectorización del fondo de valle del río Saja en Cantabria (Norte de España) para el estudio de su vegetación y dinámica vegetal en el período 1950-2010 - Nieto Tejera, Cristina (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
The aim of the research taking place is to analyse the existing vegetation and its dynamics from the fifties, in the bottom part of a river valley in Cantabria, in the North of Spain. The study of vegetation is currently a topic of high relevance, as its condition may determine trends and things like water quality, habitat for other species and the welfare of the human being, including some of its many capabilities. In areas of high human pressure, vegetation has been (and it is even now) affected considerably since historic times. The result is that there are some areas where the conservation level is high, other areas with a poor conservation level and other, the most abundant, under high deterioration. This is determined not only by its abundance or lack, but the composition of the formations. The goal is to characterize these formations and determine its most influential elements and their main threats, so that it can serve as a guide to take future action on them.